2012
DOI: 10.2139/ssrn.2082896
|View full text |Cite
|
Sign up to set email alerts
|

Product Innovation in a Vertically Differentiated Model

Abstract: We study the licensing incentives of an independent input producer owning a patented product innovation which allows the downstream …rms to improve the quality of their …nal goods. We consider a general two-part tari¤ contract for both outside and incumbent innovators. We …nd that technology di¤ usion critically depends on the nature of market competition (Cournot vs. Bertrand). Moreover, the vertical merger with either downstream …rm is always privately pro…table and it is welfare improving for large innovati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 11 publications
(18 reference statements)
0
1
0
Order By: Relevance
“…Meanwhile, Filippini and Vergari (2012) showed that in the competition of Bertrand differentiated goods oligopolistic companies, innovation owners are not interested in disseminating knowledge but prefer granting exclusive innovation rights based on licences, which promotes product differentiation. Brander and Spencer (2015) showed that Bertrand companies are always more likely to differentiate their products than Cournot companies, while Bertrand companies are less efficient.…”
Section: The Models Of the Industrial Organisation Theorymentioning
confidence: 99%
“…Meanwhile, Filippini and Vergari (2012) showed that in the competition of Bertrand differentiated goods oligopolistic companies, innovation owners are not interested in disseminating knowledge but prefer granting exclusive innovation rights based on licences, which promotes product differentiation. Brander and Spencer (2015) showed that Bertrand companies are always more likely to differentiate their products than Cournot companies, while Bertrand companies are less efficient.…”
Section: The Models Of the Industrial Organisation Theorymentioning
confidence: 99%